Analisis Informasi Citra Anatomi Ureter antara Safire dengan Filtered Back Projection pada Teknik Tracking CT Urologi Klinis Hidronefrosis - Zakiah, Putri Vina; Rasyid, Rasyid; Prastanti, Agustina Dwi; Sulistiyadi, Akhmad Haris; Sudiyono, Sudiyono; Susanti, Maya (Jurnal Imejing Diagnostik (JImeD), 2025)
Background: Clinical CT-Scan Examination and Noise Reduction in Hydronephrosis. Non-contrast CT-Scan examination is used to diagnose hydronephrosis and enhance diagnostic information in CT Urology tracking. However, CT Urography images often contain high noise levels due to examination parameters and patient size variations, which can obscure small anatomical details like the ureter. To improve image quality, reconstruction algorithms such as Filtered Back Projection (FBP) and Iterative Reconstruction (IR), particularly SAFIRE, are used alongside denoising techniques to reduce noise while preserving diagnostic information.This research aims to find the most optimal reconstruction algorithm for processing images regarding ureter anatomical information in tracking CT Urology techniques for clinical hydronephrosis.Methods: This is a quasi-experiment using the static group comparison method. Non-contrast CT (NCCT) Urology examination images in hydronephrosis patients were processed with FBP and SAFIRE strength 3 reconstruction algorithms. Assessment of anatomical image information analysis was conducted quantitatively by measuring noise and assessing anatomical information by respondents.Results: The results of this study are differences in anatomical information on Urology CT tracking images with variations in FBP and SAFIRE reconstruction algorithms with a p-value of 0.00 < (0.05 The study results showed significant differences in ureter anatomical information between CT Urology tracking images reconstructed with FBP and SAFIRE algorithms (p-value = 0.00 < 0.05). The alternative hypothesis was accepted, indicating that SAFIRE is more effective than FBP in reducing noise in CT Urology tracking images.Conclusions: SAFIRE produces higher image quality and lower noise in non-contrast CT Urology.